1980
DOI: 10.1128/iai.27.3.1012-1022.1980
|View full text |Cite
|
Sign up to set email alerts
|

Rabies serogroup viruses in neuroblastoma cells: propagation, "autointerference," and apparently random back-mutation of attenuated viruses to the virulent state

Abstract: Each of several strains of fixed rabies virus was found to replicate to high titers in C1300 mouse neuroblastoma (clone NA) cells, without adaptation. Rabies serogroup Lagos bat, Mokola, and Duvenhage viruses also replicated efficiently in NA cells. Kotonkan and Obodhiang viruses replicated efficiently after adaptation, to titers not previously obtained in vitro. Infection in NA cells was frequently more cytopathic than in BHK-21 cells, allowing titration of Kotonkan and Obodhiang viruses by plaque assay. Duve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Kaplan et al reported that all of the nude mice they infected with BHK-HEP virus died 12 to 18 days after injection and that the virus killed about 80% of ICR Comparison of these data with our results shown in Tables 1 and 2, indicates that CE-HEP virus, the vaccine strain in Japan, is a highly attenuated one. When CE-HEP virus was passaged in NA cells three or more times, it killed adult mice (4-week-old), and this was in agreement with the Clark's results (3,4). Unlike the CE-HEP virus passaged in brains of suckling mice, however, the virulent NA-HEP virus showed death patterns of the autointerfering type.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Kaplan et al reported that all of the nude mice they infected with BHK-HEP virus died 12 to 18 days after injection and that the virus killed about 80% of ICR Comparison of these data with our results shown in Tables 1 and 2, indicates that CE-HEP virus, the vaccine strain in Japan, is a highly attenuated one. When CE-HEP virus was passaged in NA cells three or more times, it killed adult mice (4-week-old), and this was in agreement with the Clark's results (3,4). Unlike the CE-HEP virus passaged in brains of suckling mice, however, the virulent NA-HEP virus showed death patterns of the autointerfering type.…”
Section: Discussionsupporting
confidence: 85%
“…(b) Lanes 1 to 4 and 6 to 12 are the patterns of the passage 6 NA-HEP fractions Nos. 2,4,6,8,10,12,14,16,18,20, and 23 in Fig. 3, respectively.…”
Section: Ce-hep Virus Infection Of Nude Micementioning
confidence: 94%
See 2 more Smart Citations
“…Mechanisms of the increase in neurovirulence after passage in neural cells are still speculative. Clark (2,3) reported rapid increases in neurovirulence of rabies virus by passage in mouse brain or in neuroblastoma cells in vitro, and suggested random mutation followed by selective replication of the mutant with neurotropic properties as a mechanism responsible for the increase in neurovirulence. Selective replication of virulent clones of CDV in the process of adaptation was also suggested by Appel (1).…”
Section: Neurovirulence Of Adapted Viruses In the Mousementioning
confidence: 99%